Proteome dataset of mouse macrophage cell line infected with tick-borne encephalitis virus - Rusanov, A L; Stepanov, A A; Zgoda, V G; Kaysheva, A L; Selinger, M; Maskova, H; Loginov, D; Sterba, J; Grubhoffer, L; Luzgina, N G (Data in brief, 2020)
We report the proteomic datasets on the mouse macrophage cell line PMJ2R infected with tick-borne encephalitis virus (TBEV) for two and six days. Data were acquired using shotgun ultra-high resolution mass spectrometry. Peptide identifications were done using the Mascot version 2.4 (Matrix Science), and quantification was performed by a label-free approach. Protein profiles of early (two days) and late (six days) stages of infection were compared between each other and the respective control samples. Protein profiles of infected and control samples differed in the number of identified proteins and their relative abundances. Proteins detected in the TBEV-infected cells were involved in various processes related to the infection, including defense response against the virus, regulation of viral process, negative regulation of viral genome replication, RNA binding, or innate immune response. Also, proteins specific for the early and late stages of infection were identified.
Keywords: Protein; Label-free quantification; Proteomics; Mass spectrometry; Mouse macrophage cell line; TBEV